Pink urine. (November 2014) - Verhoeven, E.; Capron, A.; Hantson, P.
Abstract A 55-year-old man was admitted after a suspected hypnotic overdose of valerian extracts. In addition to altered consciousness, the first clinical symptoms included not only diffuse rash on the face, trunk, and limbs, but also an inspiratory dyspnea with a marked hypoxemia. A major laryngeal edema was noted during orotracheal intubation. After correction of hypoxemia, the patient became agitated and propofol was administered by continuous infusion. In addition, the patient passed pink urine staining the urine collection bag. The presence of an unidentified toxic substance was suspected.